Pulpit and Press: Denominational Dynamics and the Growth of Religious Magazines in Antebellum America. (October 2013) - Goldstein, Adam; Haveman, Heather A.
Religious economies theory, which views religious organizations as akin to single-unit firms competing for adherents in local markets, has three shortcomings that we solve by reconceptualizing religious organizations and developing a new theory of religious mobilization. First, we treat religious organizations as multi-unit entities operating in interdependent markets in a national field. Second, we incorporate insights from social movement theory to challenge the exclusive focus on the impetus to mobilize (competition) by also considering the capacity to do so (resources). Third, we consider competition within organizations as well as between them. To analyze mobilization directly, we study a key religious resource, magazines. We analyze original data covering virtually all faiths and affiliated magazines in antebellum America, a time of great religious ferment. Consistent with our conception of religious organizations, we find that competition played out mostly within a national field. Consistent with resource mobilization theory, we find that the geography of religious mobilization reflected variations in the availability of resources more than variations in the intensity of competitive pressures. Conceiving of religious organizations as translocal movement organizations rather than local firms better accounts for their behavior. Our analysis sheds light on group dynamics in general by revealing how translocal groups in modern societies mobilize and build identity through group media.